Analisis Risiko Kesehatan Lingkungan Konsentrasi Mangan dalam Sayuran dan Air terhadap Kesehatan Masyarakat - Ukik Agustina; Yudi Iskandar; Fajar Nugraha; Puteri Inandin Nabiha; Sadono Setyoko; Dortua Lince Sidabalok; Anggun Emelia; Astrid Salome Evelina; Endang Krisnawaty; Devina Lenggo Putri; Fathimi Fathimi; Abdul Rahman (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: The research aimed to analyze the environmental health risks of manganese concentration in vegetables and water on public health.Methods: The research used cross sectional study with 138 households. Water analysis using spectrophotometric methods and for vegetable samples using the wet destruction method. The environmental sample consisted of 3 vegetables (spinach, kale and mustard greens), 3 river water and 13 resident ground water.  Results: The Mangan concentration on 3 vegetable samples (spinach, kale and mustard greens) had the same result, 0.1 mg / L. The results of manganese measurements concentration in river water were 0.2 mg / L, 0.4 mg / L and 0.4 mg / L. The average manganese concentration in 13 groundwaters were 0.32 mg/L, 0 mg/L- 1.1 mg/L.Conclusion: The RQ calculation result for vegetables and drinking water was <1 which meant that the community's manganese intake from vegetables (spinach, kale, mustard greens) and drinking water were still within safe limits.